Pengalaman Guru dalam Meningkatkan Keterampilan Mengembangkan Ide Pokok Menggunakan Digitalisasi Gambar Berseri (Digibase) - Eka Budi Nugraha; Banun Havifah Cahyo Khosiyono (Universitas Cokroaminoto Palopo, 2023)
The subject of this research is 29 fifth-grade elementary school students. The instruments employed consist of 1) a written test to assess cognitive abilities, 2) an affective observation sheet to evaluate attitudes, and 3) an observation sheet for products and performance to assess students' writing skills. The objectives of this research are 1) to improve the skills of developing main ideas and 2) to create creative products in the form of comics, short stories, and simple animated videos. This study is a qualitative research in the form of best practice using Digitalized Sequential Image Media (Digibase) to improve the skills of developing main ideas in fifth grade elementary school students. The results obtained from this research are: 1) the subjects have a high ability to develop main ideas of paragraphs. This can be seen from the assessment of the products and observations that have a range of values above 90. 2) the subjects have a very high cognitive ability in finding the main ideas of paragraphs. This can be seen from the posttest scores, where all subjects scored 100. 3) the subjects have a high affective ability, which can be seen from their affective achievement scores in aspects of mutual respect and responsibility that have a range of values of 79 and 83. From the results above, it can be concluded that the use of Digitalized Sequential Image Media (Digibase) can improve the skills of developing main ideas. Researchers found that in using Digibase media, it should be accompanied by specific teaching methods or models to make it more effective. In this case, the researchers combined it with a differentiated learning methods in the teaching process, with the aim of implementing Kurikulum Merdeka in learning.